What You Don’t Know May Be Good for You - Hörner, Johannes; Samuelson, Larry (American Economic Review, 2026)
We consider an economy in which long-lived experts are matched with short-lived clients. Experts choose the type of client with whom they match, unobserved by the market. The interaction outcome depends on both the expert’s and the client’s type. We study the effects of supplying information about otherwise unobservable outcomes, such as “medical report cards,” to help clients identify better experts. Such information can lead to inefficient matches, as experts reject risky clients to build their reputation. Hence, information can reduce welfare. Withholding information can mitigate these perverse incentives at the cost of misallocating experts known to be inept. (JEL C78, D82, D83)